(untitled) (Bangladesh Journal of Medical Science, 2022)
Background: Stapled Hemorroidectomy is more popular alternative, has higher safety profile, and quickly established than the open Hemorroidectomy procedure. Objective:The study aimed to compare between the early post-operative outcomes of open haemorrhoidectomy and stapled. Methods:A total of 50 patients between the age group 20 to 70years who were diagnosed with grade 3 and grade 4 hemorrhoids, were divided into two groups equally. Stapled haemorrhoidectomy contains 25 Patients undergoing and Open haemorrhoidectomy contains 25 Patients. Comparative analysis between the two groups were done based on student’s T test using SPSS 24 software version. The level of significance was set to 5% (p < 0.05). Results: There were 52% males and 48% females in Stapled haemorrhoidectomy groups and 64% males and 36% females in open haemorrhoidectomy group. 48% patients had grade 3 and 52% had grade 4 haemorrhoids in Stapled haemorrhoidectomy groups, and 44% had grade 3 and 56% had grade 4 haemorrhoids in open haemorrhoidectomy groups. In 16% of patients in stapled haemorrhoidectomy group and 24% of patients in open haemorrhoidectomy group blood loss was seen. In 12% of patients with staple haemorrhoidectomy and in 20% of patients with open haemorrhoidectomy was necessary supportive stitching. 52% of patients in open haemorrhoidectomy was observed residential prolapse but not in stapled haemorrhoidectomy patients. In the stapled group the duration of hospital stay (in days) was 1.96±0.82 days as compared to 3.98±0.78 days in the open group. Comparing to only 4% in the open group, 80% patients were discharged within 2 days in stapled group. In the open group at the end of 4 days 72% were discharged. Conclusions: Open haemorrhoidectomy at Milligan-Morgan is not easy as stapled haemorrhoidectomyinvolves shorter operation, fewer postoperative pain and an analgesic need, shorter hospital stays and a faster rehabilitation, earlier work back, the study confirms. Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 438-443